UPAYA PONDOK PESANTREN DALAM PEMBINAAN SANTRI SEBAGAI DA’I DI KECAMATAN BARUMUN TENGAH KABUPATEN PADANG LAWAS - Maslina Daulay (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2015)
Development of students that lead to the formation of Dai that the curriculum, and extracurricular activities. The curriculum used in boarding schools is twofold: National curriculum and curriculum of boarding school. The activity of  Extracurricular are the activities carried out outside the hours of formal (school). The Implementation of activities supported by two factors: the factors supporting and inhibiting factors. A supporting factor are including cooperation leaders on with local communities, a factor against the development needs of students, students against pollutes obedience, the motivation of santri who have the talent. Inhibiting factors are the lack of facilities and boarding school facilities, Inhibiting factors is the lack and facilities of boarding school facilities, the lack of professional development, the different of factors education the number of activities imposed on boarding school.